Raising Awareness About Violent Language Portrayed in Media Content by Implementing a CML Pedagogical Intervention in an EFL Class (2020)
ABSTRACT: This action research intended to raise awareness about violent language portrayed in media content by implementing a CML pedagogical intervention in an EFL class in the rural area of Rionegro, Antioquia, Colombia. The study follows Thoman and Jolls (2008) pedagogical proposal for teachers to implement CML lessons. Accordingly, the Empowerment Spiral framework was taken into consideration to facilitate the design of the lessons to promote critical stances particularly related to violent language in media. The results suggest that the implementation of CML was helpful in providing opportunities for learners to assess and challenge media messages and assess hidden values. Admittedly, the study was less effective in helping students establishing personal connections with the use of vulgar language.